Standard test method for alternating current magnetic properties of materials using the wattmeter-ammeter-voltmeter method, 100 to 10 000 hz and 25-cm epstein frame (American Society for Testing and Materials, 2005)
This standard is issued under the fixed designation A 348 / A348M; the number immediately following the designation indicates the year of original adoption or, in the case of revision, the year of last revision. A number in parentheses indicates the year of last reapproval. A superscript epsilon (e) indicates an editorial change since the last revision or reapproval.